View looking West; Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Wilson and Johnstone, Trinidad, 2010)
Photo showing an aerial view of Port of Spain, Trinidad. Mountains, buildings and vegetation are visible in the photo.
Colour: Black and White ; Style: Landscape ; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Port of Spain; Buildings, Port of Spain